1999
DOI: 10.1007/bf02344462
|View full text |Cite
|
Sign up to set email alerts
|

Safer sex strategies for women: The hierarchical model in methadone treatment clinics

Abstract: Women clients of a methadone maintenance treatment clinic were targeted for an intervention aimed to reduce unsafe sex. The hierarchical model was the basis of the single intervention session, tested among 63 volunteers. This model requires the educator to discuss and demonstrate a full range of barriers that women might use for protection, ranking these in the order of their known efficacy. The model stresses that no one should go without protection. Two objections, both untested, have been voiced against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…35 Another safety concern that has been suggested, but only recently tested, regarding presentation of multiple preventive options has been that women offered an array of choices may opt for methods of HIV prevention that are less well established, and they may abandon options like the male condom. 36 For example, when presented with information about microbicide use, women might opt to use this less-proven method in lieu of a male condom. 37 This has been termed "migration from the male condom."…”
Section: The Theme Of Autonomy: Female-initiated Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Another safety concern that has been suggested, but only recently tested, regarding presentation of multiple preventive options has been that women offered an array of choices may opt for methods of HIV prevention that are less well established, and they may abandon options like the male condom. 36 For example, when presented with information about microbicide use, women might opt to use this less-proven method in lieu of a male condom. 37 This has been termed "migration from the male condom."…”
Section: The Theme Of Autonomy: Female-initiated Methodsmentioning
confidence: 99%
“…However, empirical evidence suggests otherwise, at least among populations other than commercial sex workers. 36,38 In an empirical study in a large sexually transmitted infection (STI) clinic in Philadelphia, Pennsylvania, Latka and colleagues 38 have shown that fears of migration from the male condom may be unfounded.…”
Section: The Theme Of Autonomy: Female-initiated Methodsmentioning
confidence: 99%
“…These results support existing behavioral intervention research involving sexual education, including sexual negotiation skills, 35 female-controlled methods, 12,36,37 and hierarchical counseling. 10,11,38 Anecdotal reports during the intervention indicated increased awareness of the importance of safer sex in their sexual relationships following the intervention, and additional condoms and N-9 spermicides were generally requested at the final session. Although trial basis use of N-9 spermicides did not result in a more favorable evaluation of specific products, participants in the intervention increased their will- ingness to use products with characteristics common to N-9 spermicides.…”
Section: Discussionmentioning
confidence: 99%
“…2 At the onset of the HIV/AIDS pandemic, safer sex interventions designed to restrict transmission of HIV and other STDs primarily relied on promoting abstinence or increasing condom use by the uninfected. Later approaches included hierarchical interventions (e.g., New York State Department of Health AIDS Institute's Hierarchical Method of Prevention), [8][9][10][11] which presented a ranking of sexual protection methods from the safest, male and female condoms, to the most risky, spermicides based on nonoxynol-9. Most evaluations of hierarchical approaches have found that male condom use continues, and the overall proportional rates of protected sex acts was significantly increased following intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation